Nepal - Can Incentives Drive Publishers to Produce Quality Reading Materials and Schools to Buy and Use Them? - World Bank (Washington, DC, 2022)
The Results in Education for All Children (REACH) Trust Fund supports and disseminates research on the impact of results-based financing on learning outcomes. This study evaluates how the use of incentives impacted the production, procurement, and utilization of supplementary reading materials in lower primary grades in Nepal. The EVIDENCE series highlights REACH grants around the world to provide empirical evidence and operational lessons helpful in the design and implementation of successful performance-based programs.